Management v izobraževanju - stališča medicinskih sester do vseživljenjskega izobraževanja v Zdravstvenem domu Maribor - Kaučič, Boris Miha (Obzornik zdravstvene nege, 2005)
The article presents management in education and education itself as one of the aspects of socialization which encompasses the achievement of knowledge and skills. In the Health Centre in Maribor we tried to assess attitudes of nurses and nursing technicians to life-long learning. For the presentation of the problem, non-experimental causal method was used. It was found out that nurses and nursing technicians appreciate professional education and learning in nursing care highly, but their active participation in the process is too low. Their use of computers and internet in the education process is too low. It is their families that entice education in the highest proportion. In relation to their education the carriers of nursing care expressed satisfaction which indicates that work posts in nursing care are adequately systemized. They also expressed their opinion that additional knowledge would be required for higher quality of work and that their home institution enablesand pays the expenses in most cases.
Keywords: Ambulantna oskrba; Ambulatory Care; ankete; education; Education, Nursing, Continuing; health care; izobraževanje; Izobraževanje, zdravstvena nega nadaljevalno; management; medicinske sestre; Questionnaires; vseživljenjsko izobraževanje; zdravstvo